Fetal stroke - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
Fetal stroke, or that which occurs between 14 weeks of gestation and the onset of labor resulting in delivery, has been associated with postnatal epilepsy, mental retardation, and cerebral palsy. The entity is caused by antenatal ischemic, thrombotic, or hemorrhagic injury. We present seven new cases of fetal stroke diagnosed in utero, and review the 47 cases reported in the literature. Although risk factors could not be assigned to 50% of the fetuses with stroke, the most common maternal conditions associated with fetal stroke were alloimmune thrombocytopenia and trauma. Magnetic resonance imaging was optimal for identifying fetal stroke, and prenatal imaging revealed hemorrhagic lesions in over 90% of studies; porencephalies were identified in just 13%. Seventy-eight percent of cases with reported outcome resulted in either death or adverse neurodevelopmental outcome at ages 3 months to 6 years. Fetal stroke appears to have different risk factors, clinical characteristics, and outcomes than other perinatal or childhood stroke syndromes. A better understanding of those risk factors predisposing a fetus to cerebral infarction may provide a basis for future therapeutic intervention trials. (C) 2004 by Elsevier Inc. All rights reserved.
Keywords: ARTERIAL ISCHEMIC-STROKE; INTRACRANIAL HEMORRHAGE; INTRAVENTRICULAR HEMORRHAGE; SONOGRAPHIC DIAGNOSIS; IN-UTERO; ALLOIMMUNE THROMBOCYTOPENIA; PERIVENTRICULAR HEMORRHAGE; INTRACEREBRAL HEMORRHAGE; CEREBRAL INFARCTION; PRENATAL-DIAGNOSIS